FAKTOR-FAKTOR BUDAYA ORGANISASI YANG BERHUBUNGAN DENGAN PERILAKU CARING PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH PETALA BUMIPROVINSI RIAU - Mitra, Desianora, Sandi Iljanto, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Caring nurse behavior is one of the behavior of organization members that influenced theorganizational culture of an institution. Hospital with caring behavior of low nurses results in lowpatient satisfaction. And the patient's interest to return to the Hospital is reduced. This study aimsto analyze organizational factors related to caring behavior of nurses in Inpatient Room of RSUDPetala Bumi Riau Province 2017.The survey was quantitative cross-sectional observationalanalysis using chi-square test, followed by multiple logistic regression test at 76 implementingnurses.Bivariate analysis shows that there is a significant relationship between risk taking,Cooperation, and training and development, with caring behavior of nurses, while Communication,decision making is a factor counfonding to caring behavior of nurses and rewards withmanagement practices are variables that are not related to caring behavior nurse.The mostdominant variable is related to caring behavior of nursesis risk taking with OR 14,013.For thatsuggested Hospital trying to increase confidence of nurses in providing services, especially forjunior nurses. That is, by making SOPs about caring behavior and incorporating caring elementsinto the assessment of nurse's performance, then the role model of senior nurse in caring behavioris needed.Keywords : Caring nurse behavior, organizational culture, communication, reward, decisionmaking, risk taking, development training, cooperation, management practice.